1979
DOI: 10.1038/bjc.1979.2
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage malignant transformation in hamster embryo cells

Abstract: Summary.-Transformation of primary hamster embryo cells was investigated using 3-methylcholanthrene (MCA), a combination of MCA and 12-0-tetradecanoylphorbol-13-acetate (TPA), and initiation with MCA or dibenz(a,h)anthracene (DBA) followed by promotion with TPA. Evidence for transformation was (a) abnormal cellular morphology, (b) increased lifespan, (c) growth in soft agar, and (d) tumour induction by s.c. inoculation into suckling hamsters.Cells treated with either MCA or MCA+TPA showed the same latent perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 7 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…The phorbol ester TPA has been shown to promote transformation in fibroblasts after carcinogen treatment in vitro (Lasne et al, 1974;Mondal et al, 1976;Poiley, 1979) and also to affect a number of cell properties in culture independently of carcinogen treatment (Weinstein et al, 1977). One of the changes demonstrated was increased PA activity (Wigler & Weinstein, 1976).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phorbol ester TPA has been shown to promote transformation in fibroblasts after carcinogen treatment in vitro (Lasne et al, 1974;Mondal et al, 1976;Poiley, 1979) and also to affect a number of cell properties in culture independently of carcinogen treatment (Weinstein et al, 1977). One of the changes demonstrated was increased PA activity (Wigler & Weinstein, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that TPA did not accelerate the acquisition of either property. However, TPA enhanced the levels of PA activity once this had started to rise ( (Wigler & Weinstein, 1976 (Poiley et al, 1979;Mondal et al, 1976;Lasne et al, 1974). However, it could be that TPA cannot affect the rate of acquisition of transformed properties in this system in which ENU is the carcinogen, as the results so far suggest (see also below).…”
Section: Discussionmentioning
confidence: 99%
“…The basic protocol used was similar to one described by Poiley et al [11] and is outlined in figure 1. 3-Methylcholanthrene (MCA) was dissolved in acetone to a concentration of 0.5 mg/ml, and the stock solution was used at a dilution of 0.1% in DMEM + 10% NBCS to give a final concentration of 0.5 pg/ml.…”
Section: Transformation Assaymentioning
confidence: 99%
“…Strict correlations between these shortterm responses and the classic long-term response, tumor promotion in the skin ofmice, have been difficult to establish, particularly in view of the extremely divergent types of responses observed in cell culture. Both suppression and enhancement by phorbol 12-myristate 13-acetate (PMA) are observed in several systems depending, at least to some degree, on the amount of time elapsed between treatments with the initiating carcinogen and PMA (2,3). Changes in the nature of the cellular response to PMA invite speculation about the role of the metabolic state in mediating these responses.…”
mentioning
confidence: 99%